Sexism Hidden in Verbal Expressions Showing Emotions in English-Vietnamese Football Newspaper Commentaries: A Critical Discourse Analysis - Ngô, Việt Tuấn (ĐHQGHN, 2015)
Nowadays, football is undeniably the most favourite sport in the world. It is not surprising that football commentaries in newspapers always interest readers. However, sportswriters’ excessively subjective ideas displayed in these commentaries are really problematic because of their negative effects on readers’ mind. This research is carried out on some of the most viewed online newspapers in English and Vietnamese. Based on the data analyzed on the basis of Fairclough’s three-dimensional framework for Critical Discourse Analysis (CDA), the research reveals the existence of sexism embedded in verbal expressions showing sportswriters’ emotions as well as certain differences of these demonstrations in English and Vietnamese football commentaries illustrated by explanations of the presence of sexism in those commentaries.